Snow White’s Characterization in Snow White and the Seven Dwarfs by Vera Southgate and Regis Maine: A Comparison from Liberal Feminists’ Perspectives - Komang Laksmi Mas Nararya Riris; Diana, Putu Bena; Ni K. Arie Suwastini (International Journal of Language and Literature, 2023)
Women in society experienced unequal treatment due to their genders which aroused women's actions to fight for opportunities. The ideology of feminism concerns the life struggles of women to encounter the patriarchal culture and reach gender equality. This study is aimed to analyze and compare the characterizations of Snow White based on feminists' perspective. The subject of this research is Snow White as the main character in two different versions. The study employed textual analysis and revealed that Snow White with positive femininity, such as beautiful, diligent, and expressive, and negative femininity, such as dependent. The data analysis will be presented in three parts, including the similarities, the differences, and the comparison of Snow White's characterizations based on feminists' perspectives. The research will follow the qualitative analysis consisting of data collection, data reduction, data display, and conclusion drawing. However, in the story by Regis Maine, Snow White is described as more feminist than Vera Southgate's character. It can be concluded that Snow White in the story by Regis Maine is more feminist than Snow White in the story by Vera Southgate due to the masculine and feminine traits which could be used to encounter the patriarchal culture and reach gender equality.